Neodontobutis lani, a new sleeper fish of the family Odontobutidae (Teleostei: Gobiiformes) from Guangxi, southern China - Zhou, Mingwei; He, Anyou; Wang, Fangxin; Li, Yusen; Li, Chenhong (Zootaxa, 2022)
A new species, Neodontobutis lani (Odontobutidae) is described from the Zuojiang River, a tributary of the Xijiang River of the Pearl River basin, at Longzhou Town, Guangxi Zhuang Autonomous Region, Southern China. This species can be distinguished from other Neodontobutis species by following characters: anterior head flat, with interorbital width / eye diameter = 1.4–1.9 (vs. less than 1.4); several rows (vs. single row) of transforming ctenii on posterior edges of body scales; sensory papilla on lower jaw arranged in two oblong clusters (vs. two single lines). It can be distinguished from Odontobutis species by: separated right and left gill membrane (vs. joined); barbel-like projection present on sensory papillae. Molecular phylogenetic analysis of 2,076 nuclear coding loci indicates that N. lani is a sister species of N. hainanensis, the only Neodontobutis species that has been described from China.